L’auteur dramatique plaidera coupable - Delphine Aebi (Criminocorpus)
The years 1940 to 1960 are for France a period of crisis; the political and social context is conducive to thought of the judgment. Many playwrights consider the relationship with their audience similar to those that are established between the accused and the judge. Four authors think this theme through and depict it: Cocteau, Aymé, Genet and Sartre. They choose a mode of expression that seems to be necessary to evoke it: the theater, which addresses easily that subject because its structure and its operation are similar to those of a court. In both cases, an audience is attending a share, before pronouncing a judgment, after exposure to a situation often characterized by conflict. However, are there not other relationships than power struggles, and should we conclude about the pessimism of these authors?